Preemptive Behavior in Sequential Tournaments - Peter-Jürgen Jost; Matthias Kräkel (Institute for the Study of Labor (IZA), 2000)
Rank-order tournaments are usually modeled simultaneously. However, real tournaments are often sequentially. We show that agents' strategic behavior significantly differs in sequential tournaments compared to simultaneous tournaments. In a sequential tournament, under certain conditions the first acting agent chooses a preemptively high effort so that the following agent gives up. In general, the principal will prefer simultaneous tournaments in which preemptive behavior is impossible.
Keywords: J31; J33; J41; 330; Preemptive behavior; rank-order tournaments; sequential tournaments; Agency Theory; Wettbewerb; Spieltheorie; Theorie; Tournament